Psychological characteristics in patients with non-cardiac chest pain - Nikolic, Gordana Miodrag; Mandic Gajic, Gordana; Tasic, Ivan; Zikic, Olivera; Tosic Golubovic, Suzana (Vojnosanitetski pregled, 2021)
Background/Aim. Chest pain of no heart origin resembles angina and when none medical reason is found, the patients are referred to psychiatrist for further assessment. The aim of this reserch was to determine psychological characteristics of the patients with non-coronary chest pain (NCCP), difference compared to the coronary patients and the predictive value of those parameters for NCCP. Methods. Fourty consecutively recruited patients without a diagnose of heart disease (NCCP group) were examined and compared to 45 coronary patients (C group). For psychiatric diagnose, the Mini-International Neuropsychiatric Interview (MINI) was used. Psychological symptoms were assessed by the Symptom Checklist-90-Revised (SCL-90R), exposure to life events was scored by the Holms &Rahe Scale and levels of anxiety and depressiveness by the Back Anxiety Inventory and Back Depression Inventory. The statistical analysis was done by using the software package SPPS17. The Student’s-t test and χ2-test were used for estimating more difference between groups while ANOVA determined parameters associated with NCCP. Results. The NCCP patients were younger (33.40 ± 5.43 vs. 48.37 ± 6.43, p
Keywords: coronary disease; chest pain; diagnosis, differential; risk factors; psychological tests; stress, psychological; anxiety; depression